A revision of the diatom genus Lyrella Karayeva (Bacillariophyta: Lyrellaceae) from the Black Sea, with descriptions of five new species - Nevrova, Elena; Witkowski, Andrzej; Kulikovskiy, Maxim; Lange-Bertalot, Horst; Kociolek, J. Patrick (Phytotaxa, 2013)
The focus of this study is the benthic diatom flora of the coastal zone of the Black Sea, in particular that of the Ukrainian part of the Crimean Peninsula. Critically revised taxa belonging to the genus Lyrella Karayeva (Bacillariophyta: Lyrellaceae) are presented. We compared information on Navicula section Lyratae, published over the last few decades, with our observations using both light (LM) and scanning electron microscopy (SEM). Lyrella taxa considered here are characterized in terms of their morphology and ultrastructure. Light and electron micrographs of holotype (where possible) and published line-drawings are provided. The nomenclature is revised and valid taxonomic names with their synonyms are proposed. Information on the taxonomy, autecology, biogeography (distribution in the Black Sea and elsewhere) and on the diversity of Lyrella taxa is presented. Comprehensive bibliography, and list of Black Sea taxa in Lyrella combined 25 species and infraspecific taxa are included. Five of these species are new: Lyrella abruptapontica sp. nov., Lyrella karayevae sp. nov., Lyrella pontieuxini sp. nov., Lyrella pseudolyra sp. nov. and Lyrella ruppelii sp. nov. In addition, six new combinations are proposed: Lyrella dilatata, Lyrella aestimata, Lyrella rudiformis, Lyrella granulata, Lyrella rattrayi and Lyrella bacillifera. Four Lyrella taxa are reported from Black Sea diatom assemblages for the first time: Lyrella barbara, Lyrella dilatata, Lyrella fogedii and Lyrella majuscula.